KOMUNIKASI PARIWISATA DI KAWASAN PURA SURANADI DALAM MENDUKUNG SURANADI SEBAGAI DESA WISATA BUDAYA - Prayitno, Joko; Mahyuni, Mahyuni (IAHN Gde Pudja Mataram, 2024)
West Lombok Regency has designated Suranadi as a cultural tourism village. One of the tourist attractions in Suranadi village is Suranadi temple. The arrival of tourists to this place causes social interaction between tourism components so that tourism communication occurs. From the researcher's observations, tourist visits not only carry out rituals but tourists also enjoy traditional culinary delights with objectives, reasons and basic argumentative factors. Relics of tradition and culture are still preserved today, including: Pujawali ceremony, ngelungsur tirtha tradition, and sacred bathing tradition. Tourism communication occurs in the form of communication: intrapersonal, interpersonal, group and mass. The impacts of tourism communication include: introducing Suranadi cultural; growing tourist interest in coming to Suranadi Village; guarantee the development of sustainable tourism, as well as the preservation of traditions and culture of Suranadi village. Based on observations, literature studies, and interviews with a number of residents, traders, and temple managers, the findings confirm that tourism communication can support the development of Suranadi as a cultural tourism village.